Micropores Induced Stereoselective Synthesis of E‐imines: Synergistic Effect between Cerium Species and Micropores in CeAlPO‐5 Molecular Sieves. Issue 14 (26th June 2019) - Jin, Yangxin; Cao, Yali; Fang, Guoyong; Ruan, Fei; Ke, Qingping
Abstract: Metal‐doped zeolitic microporous materials are often viewed as something extremely negative as catalysis for the reactions involving aromatic molecules because of severe diffusion limitation. For these reasons, many chemists aim to development of the large microporous or hierarchical micro‐mesoporous zeolites as supports that allow for the access of the "bulky" reactants. But the "small" micropore with respect to an aromatic molecules‐involving reaction is not always a negative point. Here we employed a hierarchical micro‐mesoporous CeAlPO‐5 molecular sieve (HP‐CeAlPO‐5) as the catalyst that can catalyze stereoselective synthesis of E‐imines through the reaction of alcohols with amines. Control reactions, DFT calculations and GC‐MS analyses demonstrated that the feature of the uniform "small" micropore in the HP‐CeAlPO‐5 catalyst play a key role in the stereoselective synthesis of E‐imines. In addition, the reaction tolerates a broad range of alcohols and amines, and can be performed with as little as 0.89 mole percent catalyst in more than 90.6 percent yield and about 99.7 : 0.3 stereoselective ratio. This zeolitic catalyst provides a conceptually new and practical protocol to stereoselective synthesis of E‐imine compounds. Abstract : We employed a hierarchical micro‐mesoporous CeAlPO‐5 molecular sieve (HP‐CeAlPO‐5) as the catalyst that can catalyze stereoselective synthesis of E‐imines through the reaction of alcohols with amines. It is found that the feature of the uniform "small" micropore in the HP‐CeAlPO‐5 catalyst play a key role in the stereoselective synthesis of E‐imines.